Manajemen Risiko Bisnis BMT di Tengah Pandemi COVID-19 - Ahmadiono; M.F. Hidayatullah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The economic contraction in the MSME (Micro Small and Medium Enterprises) sector during the Covid pandemic directly impacted financial business performance. On a micro scale, BMT (Baitul Maal wat Tamwil) as a sharia microfinance institution is affected by the weakening of economic activity in the MSME sector. This is understandable because in its activities, BMT makes MSMEs its business partners. From a business aspect, the impact experienced by BMT is the emergence of various risks; increasing problematic financing, liquidity and operational risks. The results of this qualitative research show that; Firstly, business risks that arise at BMT NU Jawa timur Balung Branch and BMT UGT Nusantara Rambipuji Jember include financing risk, operational risk and liquidity risk. Financing risk is characterized by a high number of problematic financing. Meanwhile, operational risks are characterized by restrictions on access to the office, physical distancing, and increased operational costs. Meanwhile, liquidity risk is characterized by an abundance of funds in cash. Second, risk management at BMT NU Jatim Balung Branch and BMT UGT Nusantara Rambipuji Jember is carried out sequentially starting from risk identification, measurement, analysis and control activities. Based on this process, tactical steps are then developed to handle each aspect of risk. Financing risks include financing moratorium steps, intensive collection, restructuring and creating reserves for losses. Operational risks are approached by the issuance of new rules regarding office operating systems and rules related to the implementation of Health procedures.